(untitled) (Research, Society and Development, 2022)
Brazil has great potential in renewable energies, especially hydro, wind and, due to high levels of insolation, solar energy. Thanks to this characteristic, the country has been discussing ways of investing in this new technology in recent years, following the direction taken by other countries that, even with lower solar potential, stand out in photovoltaic generation, as is the case of some European countries. Since 2012, Brazil has been discussing some ways to encourage the insertion of photovoltaic solar energy in the national electricity matrix through a set of elements such as new regulations and the opening of auctions. The main objective of the research is to analyze, through simulations, the technical and economic possibilities for the implementation of photovoltaic systems in Gurupi compared to the implementation of the conventional distribution network between the years 2020 to 2021. The research is classified as documentary and exploratory, with a qualitative approach, since they will be collected on the municipality’s Transparency Portal and on the website of Energisa, which is the current energy distributor in the state, in the period studied. It is concluded with the research that the expense with photovoltaic energy generation equipment is paid with 5 years compared to conventional generation.